2015 Social Accounting Matrix for Tanzania - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
This data study includes social accounting matrix (SAM) for Tanzania for the year 2015. The SAM is an extension of the Standard Nexus structure. It consists of 68 activity sectors, 70 commodity sectors, three types of factors of production: labor (rural and urban disaggregated by level of education), land, and capital (disaggregated by crops, livestock, mining and other sectors). The household sector is divided spatially into urban and rural households. Rural households are further disaggregated into households that earn crop and/or livestock incomes (i.e., farm households) and those that do no earn incomes from either source (i.e., nonfarm households). Households are further disaggregated into per capita expenditure quintiles. This SAM allows analyzing issues at the detailed level and to better understand the potential impacts of policy changes for both better off and more vulnerable households.